Situating an Informal Funds Transfer System in Islamic Legal Theory: The Origin of Hawala Revisited - Ali Ekber Cinar (Darulfunun Ilahiyat)
Research interest regarding hawala, an informal funds transfer system, has been growing since the outset of the twentyfirst century. As for its origin, a number of authors claims that it has an Islamic origin and likens it to either ḥawāla or suftaja, which are two legal instruments elaborated in Islamic legal texts. This paper challenges that claim, comparing the hawala with ḥawāla and suftaja. The comparison reveals that the hawala does not have a specific counterpart in Islamic legal theory. On the contrary, its validity, nature, and quality are sensitive to and dependent on some minor details, and it may take the shape of diverging legal instruments from the perspective of Islamic law. Therefore, assuming that the hawala hails from and operates according to Islamic law is erroneous, and new-fashioned studies adopting historical and sociological perspectives are necessary to shed light on unanswered questions about the issue.